Synthesis and biological evaluation of niclosamide PROTACs. (15th September 2022) - Munoz, Erick; Chen, Guanglin; Hossain, Ahamed; Wu, Sitong; Oceguera Nava, Esveidy; Hang, Jasmine; Lee, Tong; Zhang, Qiang; Wang, Guangdi; Chen, Qiao-Hong
Graphical abstract: Highlights: Two niclosamide PROTACs were designed and synthesized. Antiproliferative activity was evaluated against four prostate cancer cell lines. Androgen receptor degrading capability was assessed. Selectively suppress PC-3, LNCaP, and 22Rv1 prostate cancer cell proliferation. Cannot degrade androgen receptor. Abstract: Roughly 268, 000 new cases of prostate cancer and 34, 000 deaths from prostate cancer are projected by the American Cancer Society to occur in the United States in 2022. Androgen receptor is a key protein in the proliferation and survival of prostate cancer cells and has been revealed to be overexpressed in 30% to 50% of castration-resistant prostate cancer patients. One promising approach to reducing the level of this protein is Proteolysis Targeting Chimeras (PROTACs) that is an emerging drug discovery technology. PROTACs are hetero-bifunctional molecules where one end binds to a protein of interest and the other to an E3 ligase ligand, initiating the Ubiquitin-Proteasome Pathway for protein degradation. Two PROTACs with niclosamide as androgen receptor ligand and VHL-032 as the E3 ligase ligand have been designed and synthesized for suppressing proliferation of androgen receptor-positive prostate cancer cells via degrading androgen receptor. The in vitro antiproliferative assessment suggested that they can selectively suppress PC-3, LNCaP, and 22Rv1 prostate cancer cell proliferation, but cannot inhibit DU145 cell proliferation. However, the mechanism of both compounds in suppressing prostate cancer cell proliferation is not through the AR PROTAC mechanism because they did not degrade AR in our Western Blotting assay up to 1 µM.